2005
DOI: 10.1021/es040439h
|View full text |Cite
|
Sign up to set email alerts
|

Organic Complexation of Fe(II) and Its Impact on the Redox Cycling of Iron in Rain

Abstract: More than 80% of the iron(II) present in a dilute (pH 4.5) H2SO4 solution was oxidized by hydrogen peroxide (3 microM) in 24 h, whereas in rainwater Fe(II) remained stable for days indicating that a complexed form of Fe(II) exists in rainwater that protects it against oxidation. When a rain sample was irradiated for 2 h with simulated sunlight, there was a 57 nM increase in Fe(II) resulting from photoreduction of organic Fe(III) complexes. Once irradiation ceased, the photoproduced Fe(II) rapidly oxidized back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 43 publications
3
65
0
Order By: Relevance
“…The iron solubility (% SFe) is calculated as follows: % SFe = 100 × (DFe T /Fe tot ). For some experiments, the dissolved Fe(II) (DFe(II)) was determined by a modification of spectrophotometric ferrozine method (Kieber et al, 2005). Absorbance of the iron ferrozine complex was read at 562 nm using a 1 m liquid wave-guide capillary cell attached to a JAZ spectrometer (Ocean Optics, World Precision Instruments).…”
Section: Dissolved Iron Measurementmentioning
confidence: 99%
See 3 more Smart Citations
“…The iron solubility (% SFe) is calculated as follows: % SFe = 100 × (DFe T /Fe tot ). For some experiments, the dissolved Fe(II) (DFe(II)) was determined by a modification of spectrophotometric ferrozine method (Kieber et al, 2005). Absorbance of the iron ferrozine complex was read at 562 nm using a 1 m liquid wave-guide capillary cell attached to a JAZ spectrometer (Ocean Optics, World Precision Instruments).…”
Section: Dissolved Iron Measurementmentioning
confidence: 99%
“…Nevertheless, recent works of Deguillaume et al (2010) show the daytime dissolved concentrations of Fe(II) into cloud droplets are controlled both by the initial DFe(II)/DFe T ratio upon dissolution of immersed particles and by the photochemical reactions into droplets. Moreover, Kieber et al (2005) observed that 25 % of the Fe(II)-complexing ligands in rainwater is strong enough to prevent and slow oxidation in seawater, suggesting that organic complexation enables iron to stabilize as Fe(II), probably via organic macromolecule binding ligands (Willey et al, 2008). This implies that the dissolved Fe(II) concentration could be significant in the aqueous phase even during the night due to the organic complexation.…”
Section: Iron Solubility and Redox Speciationmentioning
confidence: 99%
See 2 more Smart Citations
“…To estimate soluble Fe inputs we used our field data (Section 3.2) and assumed a solubility for dry deposition of 8 % (Baker et al, 2006b) and 14 % for wet deposition Kieber et al (2005) have reported the active photochemical production of soluble Fe(II) and also higher Fe solubilties in N. Atlantic rains, while Halstead et al (2000) report similar solubilities to those of Jickells and Spokes (2001). The solubility of Fe in rainwater is clearly an important uncertainty in these calculations and merits further study.…”
Section: Atmospheric Inputsmentioning
confidence: 99%